Everolimus-eluting bioresorabable scaffold system in the treatment of cardiac allograft vasculopathy: the cardiac allograft reparative therapy (CART) prospective multicentre pilot study. (3rd October 2022) - Pighi, M; Tomai, F; Fezzi, S; Pesarini, G; Petrolini, A; Spedicato, L; Tarantini, G; Ferlini, M; Calabro, P; Loi, B; Tovar Forero, N; Daemen, J; et al.
Abstract: Background: Cardiac allograft vasculopathy (CAV) is still the main drawback of heart transplantation (HTx) and percutaneous coronary intervention (PCI) is a palliative measure because of the high incidence of PCI failure. The bioresorbable scaffolds (BRS) could represent a potential novel therapeutic tool for the treatment of coronary obstructions in CAV. Purpose: To investigates the effects of BRS implantation in CAV patients in a Nationwide prospective study. Methods: Multicentre, single-arm, prospective, open-label study that included patients affected by advanced CAV treated with PCI and second-generation ABSORB BRS. The primary endpoint was the incidence of 12-month angiographic in-segment scaffold restenosis (ISSR). Secondary endpoints were the composite of cardiac death, myocardial infarction, and target lesion revascularisation at 12-and 36-month follow-up and the incidence of ISSR at 36 months. A paired analysis of intravascular ultrasound (IVUS) and optical coherence tomography (OCT) at baseline and follow-up was also performed. Results: Between 2015–2017 35 HTx patients were enrolled and treated on 44 coronary lesions with 51 BRS. The primary endpoint occurred in 13.5% of the lesions (5/37), with a cumulative ISSR rate up to 3 years of 16.2% (6/37).Angiographic lumen loss was 0.40±0.62mm at 12 months and 0.53±0.57mm at 36 months. Overall survival was 91.4% and 74.3%, and MACEs 14.2% and 31.4% at 12 and 36 months, respectively. At the paired intracoronary imaging analysis a significant increase of the vessel external elastic membrane area in the treated segment of the BRS was described at the OCT, while some progression of CAV was detected proximally at the IVUS assessment. Conclusions: BRS in CAV was feasible and safe, with an ISSR incidence similar to drug-eluting stents. For the first time, a positive remodeling was observed in HTx patients after PCI. Vessel enlargement and the lack of metallic stents may allow repeated PCI avoiding the vessel shrinkage caused by the addition of multiple metal layers, being CAV a complex clinical scenario with a high incidence of MACEs, mainly driven by PCI failure. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Partial funding by Abbott Vascular Italy